(untitled) (Моделювання, керування та інформаційні технології, 2019)
Mathematical model of the cable line as a part of the combined mine power network was developed, taking into account the current leakage through the human body. Simulation has shown that the cable branch of the frequency converter is characterized by an unacceptably high probability of fatal electric shock.